Politeness Principle as Seen in the Dialogue between Characters on “Freedom Writers” Movie - Salafiyah; Mariyatul Kiptiyah (Penerbit STKIP PGRI Bangkalan, 2020)
Politeness phenomenon is universal in language usage, which has been so long approached by people from the distinctive perspectives of cultures. With the advance of intercultural communication politeness can no longer be confined to the study of either the different culture, and the revaluation of politeness with the amendment of the principles for intercultural communication must be implemented for the sake of effcacious interaction. This research is conducted using descriptive qualitative method based on the theory known as Politeness Principles. The data are in form of utterances used by the characters in FREEDOM WRITERS movie. The data analysis reveals some finding covering the formulated research question